Investigating the Usefulness of Cognitive Strategies in Enhancing Critical Reading. Case Study : Master One Civilization and Literature Students at M'sila University - Bouzid Naziha, Debbache Asma (My University, 2020)
The present study attempts to investigate the usefulness of cognitive strategies in enhancing EFL students‟ critical reading. The main purpose of this research is to raise students‟ awareness of the importance of cognitive strategies in developing critical reading. It also aims to explore the extent to which cognitive strategies can improve EFL students‟ level of critical reading. Additionally, it attempts to shed light on teachers‟ role in motivating their students to read critically. This investigation was conducted among first year master students of Civilization and Literature at Mohamed Boudiaf University of M‟sila. Data of this study were collected using two questionnaires; the first one was submitted to thirty students who were chosen randomly to participate in this study, while the second one was addressed to four EFL teachers at M'sila University. It was based on the use of the descriptive research where data were collected and analyzed both qualitatively and quantitatively .The results revealed that using cognitive strategies increases the student's level of critical reading. In addition to that, teachers play a major role in motivating students to read critically through designing reading tasks that trigger students' critical thinking. Also, the findings of this study indicated that students are aware of some cognitive strategies and at the same time they ignore other important cognitive strategies that one can use to read critically. Therefore, important research implications are also suggested. It is suggested to add a new module dedicated to reading strategies. It is also suggested that critical reading skills must be emphasized and taught to students in the EFL classes because they are of a vital importance.
Keywords: Keywords: Cognitive Strategies, Critical Thinking, Critical Reading, EFL Students.